Usability and Acceptability of the Abatacept Pre-Filled Autoinjector for the Subcutaneous Treatment of Rheumatoid Arthritis - Schiff, Michael (Adv Ther, 2016)
INTRODUCTION: The purpose of the present study was to determine whether the abatacept autoinjector can be used by the intended population without patterns of preventable use errors, and is acceptable when assessed against key user needs. METHODS: Two independently conducted simulated-use studies, with no active drug administered, quantified use errors and evaluated the abatacept autoinjector and competitor devices on key attributes (comfort, control, ease of use, confidence of dose) and overall acceptability. Autoinjector preference was also assessed. Participants were patients with rheumatoid arthritis, caregivers, and healthcare professionals (HCPs). Participants were informed that a new rheumatoid arthritis autoinjector was being tested but were blinded to the intended drug and sponsor identity. RESULTS: In the formative (pre-validation) study (n = 54), two high-priority use errors occurred, both of which resulted from protocol non-compliance rather than mental confusion or physical limitations. In the summative (validation) study (n = 99), one high-priority use error occurred; this was deemed a simulated-use study artifact as participant behavior was guided by actual experience associated with the feel of drug delivery into the skin rather than by protocol, so no mitigation steps were considered necessary. Across user groups, average scores were consistently high for the pre-defined key attributes. Overall acceptability scores (7-point scale) were significantly higher for the abatacept versus competitor autoinjectors—formative study: patients 6.7 vs 5.2 (P = 0.0001), caregivers 7.0 vs 4.6 (P = 0.0093), HCPs 6.8 vs 5.1 (P = 0.0020); summative study: patients 6.5 vs 5.9 (P = 0.0404), caregivers 6.8 vs 5.8 (P = 0.0047), HCPs 6.8 vs 5.1 (P = 0.0002). The abatacept autoinjector was preferred to competitor devices: patients 85.7% vs 14.3% (P = 0.00002), caregivers 84.2% vs 15.8% (P = 0.00443), HCPs 95.0% vs 5.0% (P = 0.00004). Positive experiences with the abatacept autoinjector were attributed to the rubberized grip, device size, visualization of dose progression, button ergonomics, and ease of use. CONCLUSION: The abatacept autoinjector demonstrated usability without patterns of preventable use errors, and with high acceptability ratings across all key attributes assessed. Preference over competitor autoinjectors was due to device ergonomics, visualization of dose progression, confidence of dose delivery, and overall ease of use. FUNDING: Bristol-Myers Squibb. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12325-016-0286-9) contains supplementary material, which is available to authorized users.